渐开线斜齿圆柱齿轮齿面接触强度分析 - 李宁; 李威 (Jixie chuandong)
The total contact line length isn’t a constant value during a meshing period of helical gear pair. However the length will have an affect on the linear load which acts on helical gear pair,so the variational law of contact line length during a meshing period is analyzed.Now the contact strength of helical gear is calculated by equivalent spur gear method,but this method can’t reflect contact strength distribution of arbitrary meshing moment.The teeth of helical gear pair along contact lines are thought as cone body,according to meshing theory of helical gear and Hertz elastic contact theory,the contact strength of arbitrary meshing moment is calculated by analytical method,and the variational law of contact strength is analyzed during a meshing period. The calculated result of analytical method is verified by FEA method.